IMMUNE PREDICTORS OF FIBROGENESIS AND THEIR APPLICATION FOR NON-INVASIVE DIAGNOSTICS OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC VIRAL HEPATITIS - M. V. Shipunov; N. M. Starostina; E. L. Gelfgadt; E. R. Chernykh; A. A. Ostanin (Acta Biomedica Scientifica, 2012)
The study was devoted to development of non-invasive methods for diagnosis of liver fibrosis in patients with chronic viral hepatitis (CVH). The stepwise logistic multivariate regression analysis of biochemical (PTI, glucose, albumin, AST, LDH) and immunological parameters (the functional activity of neutrophils and monocytes, the relative content of CD8+ T- and CD19+B-cells) was used for the establishment of diagnostic model. Based on the multiple regression analysis we derived a 2 novel Integral Indexes of Liver Fibrosis (IILF-biochem and IILF-immun, respectively). It is shown that IILF-biochem allows, without resorting to liver biopsy to predict the appropriate stage of fibrosis in CHV patients with diagnostic accuracy of 86—87 %, and in combination with IILF — at 97.7 %.